Self-humidifying Pt-C/Pt-TiO2 dual-catalyst electrode membrane assembly for proton-exchange membrane fuel cells. (1st February 2017) - Yang, H.N.; Lee, W.H.; Choi, B.S.; Ko, Y.D.; Yi, S.C.; Kim, W.J.
Abstract: A high-performance Pt-C/Pt-TiO2 dual-catalyst electrode was prepared and found to exhibit excellent water production and retention in self-humidifying proton-exchange membrane fuel cells. Different weight fractions of xPt-C/(1‒x)Pt-TiO2 dual-catalyst layer were applied to both anode and cathode with fixed total Pt loadings of 0.2 mg/cm 2 and 0.3 mg/cm 2 . The dependence of cell performance on the Pt-TiO2 content in dual-catalyst electrode was highly affected by the relative humidity (RH): When the RH was lower than 60%, the cell performance was significantly affected by the Pt-TiO2 content. The ability to produce and retain water of the Pt-TiO2 catalyst layer on the anode side was very important for the zero-RH cell performance. A visual cell experiment clearly revealed that water production at the anode was highly dependent on the Pt-TiO2 content in the Pt-C/Pt-TiO2 dual layer on the anode side. A half dual-layer experiment involving the Pt-TiO2 on the cathode side alone strongly suggested that zero-RH operation is impracticable. The Pt-TiO2 in the dual layer at the anode produces water consuming the H2 and O2 crossing the membrane from the cathode, resulting in excellent cell performance under zero RH. The Pt-C/Pt-TiO2 ratio must be optimized in terms of the water-production and retention ability. Highlights: High Performance Pt-C/Pt-TiO2 dual catalyst was sandwiched between Membrane and GDL. It exhibits excellent water producing and retention ability under zero humidity. Pt-TiO2 layer at anode is critical in the aspect of water production and retention. Water produced at anode is transported into flow channel and humidifies hydrogen.